Writing matters: increasing undergraduate cell biology literacy through writing-to-learn activities-dataset - Balgopal, Meena M.; Casper, Anne Marie A.; Laybourn, Paul J.; Birsch, Ellen; Wallace, Alison M.; Dahlberg, Steven (Colorado State University. Libraries, 2015)
Biology educators need instructional strategies to improve student learning and achievement, especially in foundational courses when students are presented with vast amounts of content knowledge. Writing-to-learn (WTL) tasks in lecture courses can help biology students improve the quality of their arguments and increase content knowledge. WTL activities can model how scientists use inductive reasoning to design studies and arguments; encourage revision of ideas; support peer review and discussion; and help with writing-to-communicate tasks. Our WTL interventions include the use of graphic organizers, iterative writing, peer evaluation, and self-evaluation. We examined the effects of WTL on content knowledge, performance (grades), and argumentation. WTL is associated with 1) increased use of abstract concepts over the course of the semester in two WTL interventions (intense and moderate); 2) increased performance for some students (first generation, women, and minorities); and dialectical argumentation (persuasive) compared to demonstration arguments (expository).
Writing-to-learn activities
Zip file includes: • Spreadsheet (with demographic data and general grades) • Spreadsheet with Graphic Organizer data • AAAS/NSF PI Conference paper 2016 • NARST Conference paper 2015 • Cell Biology Concept Survey • Cell Biology WTL Peer Eval Rubric • Cell Biology WTL Grading Rubric • Cell Bio WTL Assignments 1, 2, and 3.
Department of Biology
Graduate Degree Program in Ecology
Keywords: student learning; achievement; foundational courses; WTL; studies; arguments; writing